A comprehensive and efficient daily quality assurance for PBS proton therapy. (6th February 2017) - Actis, O; Meer, D; König, S; Weber, D C; Mayor, A
Abstract: There are several general recommendations for quality assurance (QA) measures, which have to be performed at proton therapy centres. However, almost each centre uses a different therapy system. In particular, there is no standard procedure for centres employing pencil beam scanning and each centre applies a specific QA program. Gantry 2 is an operating therapy system which was developed at PSI and relies on the most advanced technological innovations. We developed a comprehensive daily QA program in order to verify the main beam characteristics to assure the functionality of the therapy delivery system and the patient safety system. The daily QA program entails new hardware and software solutions for a highly efficient clinical operation. In this paper, we describe a dosimetric phantom used for verifying the most critical beam parameters and the software architecture developed for a fully automated QA procedure. The connection between our QA software and the database allows us to store the data collected on a daily basis and use it for trend analysis over longer periods of time. All the data presented here have been collected during a time span of over two years, since the beginning of the Gantry 2 clinical operation in 2013. Our procedure operates in a stable way and delivers the expected beam quality. The daily QA program takes only 20 min. At the same time, the comprehensive approach allows us to avoid most of the weekly and monthly QA checks and increases the clinical beam availability.